2017
DOI: 10.1002/ece3.3069
|View full text |Cite
|
Sign up to set email alerts
|

Assessing patterns of genetic admixture between sheep breeds: Case study in Algeria

Abstract: In developing countries, cross‐breeding between local breeds and indigene or exotic breeds represents one of the main threats to the livestock diversity, leading to genetic dilution and loss of unique allelic combination underlying essential local adaptive traits. In this study, two Algerian sheep breeds, known to be highly admixed, were considered as a case study, to demonstrate how combination of different methodologies coupled with the use of specific softwares can be efficient to assess the spatial structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The weak geographical distribution of the genetic diversity found in the current study is consistent with previous studies on sheep breeds of Algeria using microsatellite data [ 60 ]. In addition, using single nucleotide polymorphisms, Belabdi et al [ 21 ] revealed a high level of homogenization, such that some breeds with different origins appeared to be genetically undistinguishable.…”
Section: Discussionsupporting
confidence: 92%
“…The weak geographical distribution of the genetic diversity found in the current study is consistent with previous studies on sheep breeds of Algeria using microsatellite data [ 60 ]. In addition, using single nucleotide polymorphisms, Belabdi et al [ 21 ] revealed a high level of homogenization, such that some breeds with different origins appeared to be genetically undistinguishable.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, sampling must be sufficiently broad to cover the global range of the breeds. Only this type of sampling will make it possible to really grasp the situation, knowing that a whole range of situations can be encountered between the preserved populations and the diluted populations [46]. The current cost of genetic chips is hardly compatible with the need for broad sampling, and once again emphasizes the appeal of using microsatellites to provide a first rough, but broad picture of the national situation (see [47]).…”
Section: Resultsmentioning
confidence: 99%
“…However, the differentiation of overall Maghrebin from Egyptian and Libyan sheep with affinity to Middle Eastern and Asian breeds may suggest two complementary hypotheses. According to the first hypothesis, the Tunisian and Algerian Barbarines are influenced by local thin-tailed breeds by genetic intermixing of fat- and thin-tailed breeds that appears to be a common feature in North African sheep, especially in the northwestern region ( 28 , 52 , 53 ). The second hypothesis suggests that the geographic isolation by adaptation to different eco-climates as well as different cultural practices have differentiated native sheep populations ( 22 ).…”
Section: Discussionmentioning
confidence: 99%